IMPLEMENTASI DISTIBUSI PUPUK BERSUBSIDI BERDASARKAN PRINSIP ENAM TEPAT DAN PEMANFAATANYA PADA USAHATANI PADI SAWAH DI DESA BENTE DAN DESA RANGKA KECAMATAN KABAWO KABUPATEN MUNA - Weni Fitriani; La Nalefo; Edy Syah Mihrad (Department of Agricultural Extension, Faculty of Agriculture, Halu Oleo University, 2026)
The distribution of subsidized fertilizers is a strategic government policy aimed at improving farmers' access to agricultural inputs and enhancing lowland rice productivity. The effectiveness of this policy depends not only on the efficiency of the distribution system but also on the proper utilization of fertilizers in accordance with recommended agricultural practices. This study aimed to analyze the implementation of subsidized fertilizer distribution based on the Six Right Principles and to describe its utilization in lowland rice farming in Bente and Rangka Villages, Kabawo District, Muna Regency. A quantitative approach employing a survey method was applied. A total of 56 farmers were selected using proportional random sampling from a population of 125 subsidized fertilizer recipients. Data were collected through structured interviews, field observations, and documentation, and were analyzed descriptively using frequency distributions and percentages. This study offers a more comprehensive perspective by integrating the evaluation of subsidized fertilizer distribution based on the Six Right Principles with fertilizer utilization practices at the farm level. The results revealed that the implementation of subsidized fertilizer distribution successfully fulfilled five of the six indicators, namely the right place (85.71%), the right type (100%), the right price (78.57%), the right time (71.43%), and the right target (100%). However, the right quantity indicator remained relatively low (44.64%) because the allocated fertilizer was insufficient to meet farmers' actual needs. Regarding fertilizer utilization, all respondents applied the recommended types of fertilizers (Urea and NPK), while 69.64% applied the recommended fertilizer dosage and 76.79% applied fertilizers at the appropriate time. The insufficient quantity of subsidized fertilizers prompted some farmers to adjust fertilizer application rates, indicating that the effectiveness of fertilizer utilization was strongly influenced by the quality of the distribution system. Therefore, improving the effectiveness of the subsidized fertilizer policy requires refining allocation mechanisms based on site-specific fertilizer requirements, regularly updating the electronic Definitive Group Needs Plan (e-RDKK) database, and strengthening the role of agricultural extension workers in promoting balanced fertilization practices to enhance the productivity and sustainability of lowland rice farming.